Graphene Quantum Dots from Polycyclic Aromatic Hydrocarbon for Bioimaging and Sensing of Fe3+ and Hydrogen Peroxide. (7th August 2013) - Zhou, Li; Geng, Junlong; Liu, Bin
<x xml:space="preserve">Abstract</x> An easy approach for large‐scale and low‐cost synthesis of photoluminescent (PL) graphene quantum dots (GQDs) based on the carbonization of commercially available polycyclic aromatic hydrocarbon (PAH) precursors with strong acid and followed by hydrothermal reduction with hydrazine hydrate is reported. Transmission electron microscopy (TEM) and atomic force microscopy (AFM) characterizations indicate that the size and height of GQDs are in the range of 5–10 nm and 0.5–2.5 nm, respectively. PAH, which has more benzene rings, generally forms GQDs with relatively larger size. The GQDs show high water solubility, tunable photoluminescence, low cytotoxicity, and good optical stability, which makes them promising fluorescent probes for cellular imaging. In addition, the fluorescence of GQDs shows a sensitive and selective quenching effect to Fe3+ with a detection limit of 5 × 10−9m. By combination with the Fe2+/Fe3+ redox couple, the PL GQDs are able to detect oxidant, using H2O2 as an example. This study opens up new opportunities to make full use of GQDs because of their facile availability, cost‐effective productivity, and robust functionality.